A culture of ambiguity : an alternative history of Islam - Bauer, Thomas, 1961 September 27- (Columbia University Press, 2021)
"Islamic cultures seem to be ideal examples of cultures dominated entirely by religious norms. But in this sense the modern understanding of Islam differs markedly from that of the classical period (i.e., the premodern until well into the nineteenth century). Whereas modern fundamentalist movements aim at the greatest possible legitimization of religious norms throughout the entire society and see this as being the most Islamic structure (and are confirmed in this view by the western public opinion of Islam), a glimpse at premodern Islamic cultural forms offer a much more complex picture. Already the extraction of norms from the authoritative texts reveals itself to be an exacting process of disambiguation that included several subjective processes and rational procedures. The fact that these procedures led to a juxtaposition of competing norms was widely accepted--see the much quoted prophet's hadith "Difference of opinion is a mercy for my community." This kind of tolerance of ambiguity manifests itself not only in Islamic law but also in many other spheres of Islamic scholarship (for example, in Qur'an exegesis and in linguistics), in several literary genres, and also in the mentality of social conditions and of the people themselves, which included tolerance of religious minorities, sympathetic attitudes towards foreigners, and high social mobility). Symptomatic is also the considerably conflict-free coexistence of religious and secular discourses in classical Islamic culture, which stands in striking contrast to the inseparability of Islam and the worldly sphere postulated today. Under these specific conditions Islam was spared many of the crises of the Occident, but herein also lies an important cause of the current conflicts between Islam and the modern West. The collision of Islam with a culture that hardly knew such a tolerance of ambiguity and tended to reject it had to lead to a reformulation of the fundamentals of Islam in the form of ideologies that were more in conformance with modernity, which, in both their pro-western liberal form as well as in their Islamicist variation, are equally characterized by the rejection of their own cultural traditions. Beyond the investigation of cultural ambiguity in Islamic history, this interdisciplinary project tests out to what degree the investigation of the (in)tolerance of ambiguity allows relevant cultural-historical approaches to be established"--